PERAN KOMITE MADRASAH TERHADAP PROSES MANAJEMEN SARANA PRASARANA DI MTSN NGKERAN - Selian, Sahudin; Salfiyadi, Teuku; Syahrin, Alfi; Iskandar, Iskandar; Marsithah, Iis (Universitas Indraprasta PGRI, 2025)
This study was conducted as a way to describe the role of the madrasah committee in the management process at the State Junior High School (MTsN) Ngkeran, Southeast Aceh, especially regarding its role as an assessor, an acceptor, a control and a mediator. This study uses qualitative with a descriptive approach. While data collection uses interviews, observations and documentation. This data analysis technique uses data collection, data reduction, data analysis, data presentation and drawing conclusions. The results of the study show that the Madrasah Committee has an important role in the management process of the madrasah, especially in managing facilities and infrastructure, finance, infrastructure, curriculum, personnel, and public relations of the residents of Darul Amin Village, Lawe Alas District, Southeast Aceh Regency in general. The role of the Madrasah Committee in the process of controlling infrastructure at MTsN Ngkeran, Southeast Aceh, was made by the madrasah, the Madrasah Committee provides suggestions if there are things that need to be conveyed. And the Committee participates in implementing the program for the process of controlling infrastructure in the madrasah and the work, if the Committee is invited by the Head of the Madrasah himself.